2021
DOI: 10.3390/pathogens10121613
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors of Crimean-Congo Hemorrhagic Fever in Cattle of Smallholder Farmers in Central Malawi

Abstract: Crimean-Congo hemorrhagic fever virus (CCHFV) is endemic in Africa, Asia, and Eastern Europe where it circulates among animals and ticks causing sporadic outbreaks in humans. Although CCHF is endemic in sub-Saharan Africa, epidemiological information is lacking in many countries, including Malawi. To assess the risk of CCHF in Malawi, we conducted an epidemiological study in cattle reared by smallholder livestock farmers in central Malawi. A cross-sectional study was conducted in April 2020 involving seven dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…This phenomenon was reported in cattle from Pakistan (88) and was considered a reliable preventive strategy when animals from Sudan were introduced into Saudi Arabia (104). This was clearly linked to the tick burden of animals, which was also measured in some studies (33,35,(87)(88)(89)(90)(91). Conversely, some studies reported insignificant or opposite effects of acaricide treatments or tick control actions but a little information was provided on the chemicals and methods used to assess their reliability (35,87,89).…”
Section: Factors That May Promote Cchfv Enzootic Transmission In Fran...mentioning
confidence: 99%
See 4 more Smart Citations
“…This phenomenon was reported in cattle from Pakistan (88) and was considered a reliable preventive strategy when animals from Sudan were introduced into Saudi Arabia (104). This was clearly linked to the tick burden of animals, which was also measured in some studies (33,35,(87)(88)(89)(90)(91). Conversely, some studies reported insignificant or opposite effects of acaricide treatments or tick control actions but a little information was provided on the chemicals and methods used to assess their reliability (35,87,89).…”
Section: Factors That May Promote Cchfv Enzootic Transmission In Fran...mentioning
confidence: 99%
“…Several studies conducted in Africa and Asia have shown that CCHF seroprevalence significantly increases with the animal age, either in cattle, small ruminants, and camels (33,35,(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97). This correlation was mainly attributed to an increasing probability of an animal to be exposed to infected tick vectors, contract CCHFV, and develop an immune response in relation with increasing age (33). Such an additive effect of age seems obvious as antibodies are assumed to persist for a long period in animals, up to several years (98).…”
Section: Factors That May Promote Cchfv Enzootic Transmission In Fran...mentioning
confidence: 99%
See 3 more Smart Citations